Luteinizing Hormone Receptor-Stimulated Progesterone Production by Preovulatory Granulosa Cells Requires Protein Kinase A-Dependent Activation/Dephosphorylation of the Actin Dynamizing Protein Cofilin - Karlsson, Amelia B. (The Endocrine Society, 2010)
Activation of the LH receptor (LHR) on preovulatory granulosa cells stimulates the cAMP/protein kinase A (PKA) pathway to regulate expression of genes required for ovulation and luteinization. LHR signaling also initiates rearrangement of the actin cytoskeleton. Because disruption of the actin cytoskeleton has been causally linked to steroidogenesis in various cell models, we sought to identify the cellular mechanisms that may modulate reorganization of the actin cytoskeleton and to determine whether cytoskeletal reorganization is required for steroidogenesis. Herein we report that LHR signaling in preovulatory granulosa cells promotes rapid dephosphorylation of the actin-depolymerizing factor cofilin at Ser3 that is dependent on PKA. The LHR-stimulated dephosphorylation of cofilin(Ser3) switches on cofilin activity to bind actin filaments and enhance their dynamics. Basal phosphorylation of cofilin(Ser3) is mediated by active/GTP-bound Rho and downstream protein kinases; LHR signaling promotes a decrease in active/GTP-bound Rho by a PKA-dependent mechanism. LHR-dependent Rho inactivation and subsequent activation of cofilin does not involve ERK, epidermal growth factor receptor, or phosphatidylinositol 3-kinase pathways downstream of PKA. To understand the biological significance of cofilin activation, preovulatory granulosa cells were transduced with a mutant cofilin adenoviral vector in which Ser3 was mutated to Glu (S-E cofilin). Inactive S-E cofilin abolished LHR-mediated reorganization of the actin cytoskeleton and caused a 70% decrease in LHR-stimulated progesterone that is obligatory for ovulation. Taken together, these results show that LHR signaling via PKA activates a cofilin-regulated rearrangement of the actin cytoskeleton and that active cofilin is required to initiate progesterone secretion by preovulatory granulosa cells.